Review on marine energy program. (February 2020) - Abdullah, K
Abstract: As our fossil fuel is rapidly depleting, Indonesia need to explore new source of energy to support our economic development. One of this possibility come from the sea where the potential is estimated to reach 49 GW and only very small portion has been utilized. This paper describes activities related to marine energy development particularly in some selected Asian countries and the Pacific. Marine energy development described here is limited to power generation using sub-surface current and OTEC (Ocean Thermal Energy Conversation). It was the Tokyo Electric Company who started to build 100 kW OTEC on the island of Nauru in 1970, and it was the first system operating on grid. Marine energy studies, particularly on OTEC was first conducted by the IOES (Institute of Ocean Energy, Saga university). For the case of sub surface sea current research in Indonesia was first conducted by T-Files in which they constructed a 5 kW power generation and tested in Nusa Penda, Bali. Later in 2010 a 10 kW sub-surface sea current was also constructed and tested in Larantuka, Flores island. Although marine energy has been considered high cost several simulation studies in Indonesia have indicated that the cost of electricity production using OTEC could be reduced to below US$07/kWh.